Improvement of Skills English Essay Writing - N. S. Izmaylova (Научный диалог, 2018)
The article is devoted to the improvement of the quality of students’ creative works in English - mini-compositions, or essays. This type of work is becoming more and more popular in training specialties like “journalism,” “public relations,” “mass communications,” etc., which imply both creative approach and frequent contacts with foreign experts, which explains the need to be able to express their thoughts competently and interestingly not only in their native language, but also in the language of international communication. This makes this article relevant. The author gives specialists’ recommendations in the field of writing from Duke University (USA), called “Five rules of effective writing on the letter C” (“Five Cs”). The article comments in detail each of the rules with the involvement of examples from the practice of teaching writing in higher educational institutions of Russia. One student essay is also analyzed for compliance with these rules. The author concludes about the practical use of these recommendations, need for their discussion and inclusion in the criteria for evaluating student work, which has already been done in one of the Russian universities.